Barriers of Continuation of Growth Monitoring in Bara District. - S, Yogesh. (Tufts University. Tisch Library., 2019)
This poster highlights the barriers of continuation of growth monitoring in bara district.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy